Chomsky language, mind, and politics - McGilvray, James A. (James Alasdair) 1942- (Cambridge Polity Press, 2014)
Noam Chomsky is one of the most influential figures in contemporary intellectual life, known for his groundbreaking contributions to a range of fields from linguistics to political theory. This is a fully revised and updated edition of James McGilvray's highly successful introduction to Chomsky's work and thought.
Chomsky's contributions -- The mind and its sciences -- Partitioning the mind : bad and good cognitive sciences -- Human problem-solving capacities -- The science of language -- Linguistic meanings and their uses -- Chomsky on politics : some basic themes -- Language and politics : justification.
Includes bibliographical references (pages [264]-267) and index.
Keywords: Chomsky, Noam -- Philosophy; Philosophy of mind; Linguistics